Where has all the money gone? Materiality, mobility, and nothingness - Angus Cameron (Finance and Society, 2015)
This article argues that the problematic nature of money's 'location' is important to opening up its more fundamental ontology. Using examples from recent financial crises, I explore the (temporary) historical relationship between money and the nation state, the changing nature of money, and the paradoxes these produce in a world convinced that money is real and material. I conclude that whilst we cannot resolve these ingrained paradoxes, we should at the very least take account of them as we try to explain the vagaries of our money economies.
Keywords: 300; Money; territory; extraterritoriality; financialisation; mobility; ontology